ISLAMIC WEALTH MANAGEMENT TRENDS IN BIBLIOMETRIC ANALYSIS - M. Fauzan; Sugianto; Marliyah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Wealth management focuses on the management of wealth, specifically addressing Islamic wealth management in this research. The aim is to analyze the relevant literature to identify research trends in Islamic wealth management. Data was obtained from Crossref Search covering the years 2019-2024, using Harzing’s Publish or Perish (PoP) software, which was analyzed using bibliometrics with VOSviewer. The research findings from the network visualization underscore the importance of modern aspects in Islamic Wealth Management (IWM), such as profitability and intellectual capital, reflecting the increasing trend of digitalization, particularly amid the pandemic. These findings suggest that wealth managers in the Islamic finance sector should adapt digital approaches to reach a broader market segment, especially the younger generation. Policy recommendations include the necessity for support for responsible and sustainable investments, as well as the development of regulations that ensure wealth management aligns with Sharia principles. This research contributes to understanding how IWM can adapt to contemporary challenges while maintaining a commitment to social justice and economic sustainability.